Coordination Chemistry - Kumar, Ajai (Muzafffarnagar: Aaryush Education, 2023)
The content given in the book will be invaluable to teaching and learning concept of Coordination Chemistry. The questions, objective and subjective have the levels of various competition exams like IIT-JAM, CSIR-UGC (JRF/NET), GATE, IISC, BARC, TIFR, DRDO, ONGC, NTPC, NBRC etc.
Includes index
Keywords: Coordination compounds; Ligands; Transition metals